Diagnosis of Alkaptonuria after Lumbar Discectomy: Case Report and a Review of the Literature - Dolgun, Habibullah; Gurer, Bora; Sarı, Riza Onur; Yılmaz, Erdal Resit; Sekerci, Zeki (Fırat University, 2012)
Alkaptonuria is a rare autosomal recessive disorder which causes degenerative changes in cartilage, intervertebral disc and other tissues. Although intervertebral disc degeneration is common in alkaptonuria; where there are only a few patients treated surgically for lumbar disc disease. Diagnosis of alkaptonuria after black colored lumbar discectomy material is a rare condition. We present a case of alkaptonuria, in which the patient was diagnosed after lumbar discectomy.

Alkaptonüri, kıkırdak dokuda, intervertebral disklerde ve diğer dokularda dejeneratif değişikliklere neden olan nadir bir otozomal resesif hastalıktır. Alkaptonüride intervertebral disk dejenerasyonu sık olmasına rağmen lomber disk hernisi nedeniyle opere edilen hasta sayısı oldukça azdır. Siyah renkli lomber diskektomi materyalini takiben alkaptonüri tanısı konulması çok nadir bir durumdur. Bu yazıda, lomber diskektomi sonrası alkaptonüri tanısı alan bir alkaptonüri olgusu sunulmaktadır.
Lomber Diskektomi Sonrası Konulan Alkaptonüri Tanısı: Olgu Sunumu ve Literatür Derlemesi